Supporting post-exercise recovery in adolescent soccer players: A study of a locally formulated recovery drink - Nisya, Karin Zikra; Setiawan, Budi; Marliyati, Sri Anna (Journal Sport Area, 2025)
Background: Adolescent athletes are prone to exercise-induced fatigue, making effective recovery strategies essential. Although carbohydrate–protein beverages support recovery, most studies focus on commercial products, while the potential of local ingredients such as pisang raja and gulo puan in Indonesia remains underexplored. Research Objectives: This study aimed to analyze the effects of a homemade recovery drink (HRD) formulated from low-fat milk, cocoa powder, pisang raja, and gulo puan on the physical recovery of adolescent soccer athletes. Methods: A quasi-experimental design was conducted with student-athletes (aged 15–17 years) from Sekolah Olahraga Negeri Sriwijaya Palembang, divided into a control group (placebo, n = 10) and an intervention group (HRD, n = 10). The intervention was administered in a single-blind manner, with two doses provided during a 2-hour recovery window. Data collected included blood pressure, heart rate, and blood glucose. Finding/Results: The results showed no significant differences in blood pressure between the HRD and placebo groups (p > 0.05). However, significant differences were found in post-recovery heart rate and blood glucose levels (p < 0.05). The HRD group showed significantly higher post-recovery blood glucose levels (95 ± 5.77 vs. 88.5 ± 6.49 mg/dL, p = 0.022), and heart rate in this group returned closer to baseline compared to the placebo. Conclusion: The findings suggest that an HRD formulated from culturally relevant, locally sourced ingredients can effectively support post-exercise recovery in adolescent athletes by maintaining cardiovascular stability and blood glucose levels. This study highlights the potential of traditional Indonesian foods as affordable, accessible alternatives to commercial recovery products.